BENCHMARKING INNOVATION DEVELOPMENT OF BRICS AND IRAN ON THE BASIS OF KAM - Московкин, Владимир; Самсонова, Светлана (Human Geography Journal, 2015)
The Knowledge Assessment Methodology (KAM) of the World Bank and the underlying empirical research is considered. On its basis the Basic Scorecard for aggregated and integrated indicators BRICS countries and Iran is built, which showed on Russia and Brazil leadership. On the basis of the scorecard and scale levels classification of development of countries by weighted KAM-indicators  matrix of levels of BRICS countries and Iran on these indicators is constructed. Arising from Basic Scorecard unexpected results related to the large gap between China and Russia and Brazil, and the gap between China and India from Iran (in terms of KI) explained of subjective choice of three partial indicators from the three areas of knowledge. Output is seen in the account of all partial indicators of the knowledge economy and the construction of Common Scorecard.